BOUDICA AND HER RECEPTION BY BRITISH SUFFRAGETTES - Bélo, Tais Pagoto (PHOÎNIX, 2024)
This paper is about the reception of Boudica by British suffragettes, who played a prominent role in an episode that occurred during the 1st century AD, in 60 and/or 61 AD, which marked the roots of the formation of the British people. She was the queen of the Iceni tribe and led an army against the Roman Empire after her daughters were raped, and she was whipped by Roman officials. Boudica was regarded as the representative of the first women-led freedom movement. In this way, the queen of the Iceni was embraced by the suffragettes to empower and strengthen this social movement and to demonstrate the bravery of female leadership.